Proses peruraian anaerobik palm oil mill effluent dengan media zeolit termodifikasi - Melly Mellyanawaty; Firda Mahira Alfiata Chusna; Estin Nofiyanti (Jurnal Rekayasa Proses, 2019)
This work evaluated the effect of modified zeolite as microbial immobilization medium in anaerobic digestion of palm oil mill effluent (POME). The affinity of microorganisms to attach and grow on the media surface could be increased by the addition of micro-nutrient into the media. The effect of micro-nutrient addition was studied in 1000 mL Erlenmeyer flask as batch reactors. Experiments were conducted for 30 days. The concentration of soluble chemical oxygen demand (COD) in substrate was 8000 mg/L. Zeolite was impregnated with nickel (Ni) and zinc (Zn) at individual concentration of 2.7x10-3 mg Ni/g zeolite and 3.5x10‑3 mg Zn/g zeolite. The influence of each modified zeolite was determined by periodic measurement of sCOD, volatile fatty acid (VFA), pH, and biogas production. Cumulative biogas productions in this study were 252.44; 172.13; 57.70 ml from Ni-modified, Zn-modified and natural zeolites, respectively. The highest sCOD removal was obtained in reactor with Zn-modified zeolite with 38.22% removal, followed by 33.96% with Ni-modified zeolite, and 27.87% removal with natural zeolite.